2011
DOI: 10.1111/j.1365-2869.2010.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in functioning from the patient perspective using the International Classification of Functioning, Disability and Health (ICF) as a reference

Abstract: Summary We conducted a qualitative, multicenter study using a focus group design to explore the lived experiences of persons with any kind of primary sleep disorder with regard to functioning and contextual factors using six open‐ended questions related to the International Classification of Functioning, Disability and Health (ICF) components. We classified the results using the ICF as a frame of reference. We identified the meaningful concepts within the transcribed data and then linked them to ICF categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 76 publications
0
17
1
Order By: Relevance
“…The relatively small number of studies which used the person-centred approach is notable considering the emerging research which supports this approach to fully understand the person's experience [6,22,51], however, our findings provide evidence of increasing interest in the biopsychosocial and person-centred approach to healthcare. Only two papers published in 2012 met the inclusion criteria, although we identified 155 studies published in 2012 which used the ICF to study chronic conditions.…”
Section: Year Of Publicationcontrasting
confidence: 48%
See 1 more Smart Citation
“…The relatively small number of studies which used the person-centred approach is notable considering the emerging research which supports this approach to fully understand the person's experience [6,22,51], however, our findings provide evidence of increasing interest in the biopsychosocial and person-centred approach to healthcare. Only two papers published in 2012 met the inclusion criteria, although we identified 155 studies published in 2012 which used the ICF to study chronic conditions.…”
Section: Year Of Publicationcontrasting
confidence: 48%
“…In the majority of studies the average age of the participants was over 50, which is consistent with the higher prevalence of certain chronic conditions with age [46]. The younger participants represented conditions which are not agedependent including spinal cord injury [47][48][49][50], primary sleep disorder [51], multiple sclerosis [52,53], cerebral palsy [54] and Huntington's disease [55]. The participants undergoing vocational rehabilitation [56,57] and with non-specified disability [58] were also generally of a younger age.…”
Section: Resultsmentioning
confidence: 55%
“…I'm scared that I'm not going to be able to go back to my studies and go to university. (p. 199) Furthermore, using the International Classification of Functioning, Disability Health (ICF) Gradinger et al (2011) also found similar social and environmental functional deficits when exploring the lived experiences among those with primary sleep disorders such as insomnia.…”
Section: Definition Of Insomnia and Patient Illness Experiencementioning
confidence: 87%
“…The choice of six focus groups in this study was based on previous reports on ICF core set projects, where 4 to 6 focus groups were required to collect sufficient information about functioning and contextual factors to reach data saturation (e.g. Boonen et al, 2009;Coenen et al, 2011;Gradinger et al, 2011). The focus groups were organized according to three age groups (18-40 years, 41-60 years and 61 years and above).…”
Section: Designmentioning
confidence: 99%
“…In previous Core Set projects and ICF research projects, the first three steps of the meaning condensation methodology as described by Kvale (1996) was used (Boonen et al, 2009;Coenen et al, 2012;Coenen et al, 2011;Glässel et al, 2011;Gradinger et al, 2011). The essence of that method is the condensation part (i.e.,…”
Section: The Seven-steps Linking Proceduresmentioning
confidence: 99%